Role of International Organizations in Promoting Sustainable Development in Conflict-Affected Regions: Case of Luhansk Region in Ukraine - Semenenko, Inna; Halhash, Ruslan; Ivchenko, Yevhen (European Journal of Sustainable Development, 2019)
The article examines the role of international organizations in promoting sustainable development and achieving sustainable development goals (SDGs) in conflict-affected regions by providing the case of Luhansk region, which since 2014 has lost a significant part of its territory, substantial industrial potential and has got numerous political, social and economic problems due to the military conflict in the East of Ukraine. The international research has already given successful experience of role of international organizations in promoting sustainable development of various problem territories. Investigation of case of Luhansk region is structured around the analysis of presence of international organization in Ukraine as a whole and in Luhansk region as a conflict-affected area, and their activities. Such analysis allowed to distinguish the main directions of international organizations’ activities and identify the key sustainable development aspects and SDGs, the achievement of which is possible due to these activities. Even the cursory comparison of the budgets of the region and international organizations made it obvious that the local authorities are incapable of solving the emerged problems and achieving the SDGs in conflict-affected areas without assistance of international community. Keywords: conflict-affected region, sustainable development, international organizations, promoting, sustainable development goals